Review: Antibacterial activity of lime (Citrus aurantifolia L.) peel - Wibowo, Diki Prayugo; Mariani, Ria (Institute of Computer Science (IOCS), 2024)
Over the past three decades, a plethora of scientific publications have indicated that medicinal plants may offer a viable substitute for antibiotics. Research on the antibacterial activity of lime peel, or Citrus aurantifolia L., has been widely published. This review aimed to highlight the lime peel as antibacterial agents. Numerous scientific papers included for this review demonstrated the potentially effective antibacterial properties of lime peel. Strong antibacterial activity is exhibited by lime peel essential oils, extracts, and fractions. One component of lime peel essential oils that contributes to its antibacterial properties is limonene. According to this study, infections brought on some bacteria including cariogenic bacteria and acne bacteria can be treated using lime peel.